2021
DOI: 10.1093/rheumatology/keab262
|View full text |Cite
|
Sign up to set email alerts
|

A review and roadmap of the skin, lung and gut microbiota in systemic sclerosis

Abstract: As our understanding of the genetic underpinnings of systemic sclerosis (SSc) increases, questions regarding the environmental trigger(s) that induce and propagate SSc in the genetically predisposed individual emerge. The interplay between the environment, the immune system, and the microbial species that inhabit the patient’s skin and gastrointestinal tract is a pathobiological frontier that is largely unexplored in SSc. The purpose of this review is to provide an overview of the methodologies, experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 86 publications
0
6
0
7
Order By: Relevance
“…Systemic sclerosis (SSc) is a chronic systemic connective tissue disease characterized by vascular disorders and progressive fibrosis within the skin and internal organs, leading to their failure [11,12]. The gastrointestinal tract becomes involved in the disease process in about 90% of patients, which is the cause of 6-12% of deaths in SSc [12][13][14]. Etiology of this disease is not exactly known, but it is suggested that SSc occurs in genetically predisposed individuals with participation of certain environmental factors [13,15].…”
Section: Systemic Sclerosismentioning
confidence: 99%
See 4 more Smart Citations
“…Systemic sclerosis (SSc) is a chronic systemic connective tissue disease characterized by vascular disorders and progressive fibrosis within the skin and internal organs, leading to their failure [11,12]. The gastrointestinal tract becomes involved in the disease process in about 90% of patients, which is the cause of 6-12% of deaths in SSc [12][13][14]. Etiology of this disease is not exactly known, but it is suggested that SSc occurs in genetically predisposed individuals with participation of certain environmental factors [13,15].…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…The gastrointestinal tract becomes involved in the disease process in about 90% of patients, which is the cause of 6-12% of deaths in SSc [12][13][14]. Etiology of this disease is not exactly known, but it is suggested that SSc occurs in genetically predisposed individuals with participation of certain environmental factors [13,15].…”
Section: Systemic Sclerosismentioning
confidence: 99%
See 3 more Smart Citations